Valuing Air Quality Using Happiness Data: The Case of China - Xin Zhang; Xiaobo Zhang; Xi Chen (Institute for the Study of Labor (IZA), 2016)
This paper estimates the monetary value of cutting PM2.5, a dominant source of air pollution in China. By matching hedonic happiness in a nationally representative survey with daily air quality data according to exact dates and locations of interviews in China, we are able to estimate the relationship between local concentration of particulate matter and individual happiness. By holding happiness constant, we calculate the tradeoff between the reduction in particulate matter and income, essentially a happiness-based measure of willingness-to-pay for mitigating air pollution. We find that people on average are willing to pay 539 (88, or 3.8% of annual household per capita income) for a 1 μg/m3 reduction in PM2.5 per year per person.
Keywords: Q51; Q53; I31; 330; willingness to pay; hedonic happiness; air pollution; China